Comparison of Prostaglandin Analogue and Selective Laser Trabeculoplasty Capability to Maintain Intraocular Pressure Fluctuation on Primary Open Angle Glaucoma - Sara Listyani Koentjoro; Maharani Cahyono; Fifin Luthfia Rahmi (Journal of Biomedicine and Translational Research, 2017)
Background: Glaucoma patients often come with intraocular pressure (IOP) that reach target pressure, but still have glaucoma progression due to IOP fluctuation. Water drinking test (WDT) can be used as a method to predict IOP fluctuation.Purpose: To compare prostaglandin analogue (PGA) and selective laser trabeculoplasty (SLT) capability to maintain IOP fluctuation on primary open angle glaucoma (POAG).Method: This clinical experimental research was conducted at Dr. Kariadi Hospital. Subjects were POAG patients selected with consecutive sampling. Intraocular pressure was measured before and after WDT. After WDT, IOP was measured every 15 minutes until 1 hour. Peak IOP and IOP fluctuation data were collected then analyzed with t-test.Results: Forty two eyes from 30 POAG patients were analyzed. Twenty six eyes in PGA group and 16 eyes in SLT group. Most of the subjects were male with mild glaucoma degree. WDT increased IOP significantly on both groups. Mean IOP pre WDT was 14.58 ± 2.580 mmHg and 16.94 ± 2.645 mmHg in PGA and SLT groups. Mean peak IOP post WDT was 22.73 ± 4.114 mmHg and 25.75 ± 5.859 mmHg in PGA and SLT groups. Mean IOP fluctuation was 8.15 ± 4.202 mmHg and 8.81 ± 5.344 mmHg in PGA and SLT groups. Peak IOP and IOP fluctuation result analysis on both groups were not significantly different.Conclusion: Prostaglandin analogue and SLT had equal capability to maintain IOP fluctuation but still higher than normal fluctuation (>6 mmHg) that affects glaucoma progression.